Avocado (Persea americana) peel: a promising source of bioactive compounds - Oke, Morenikeji Abel; Adebayo, Elijah Adegoke; Ajisope, Nathaniel Aanu; Olowe, Busayo Mutiat; Fasuan, Oluwabunmi Susan (Frontiers in Nutrition, 2025)
In recent times, the industrial high demand for Persea americana (PA) fruits has swiftly increased its production globally. This has resulted in the excessive presence of avocado peel (AVDP) waste as an environmental pollutant since the peel is commonly discarded without any further application. AVDP has been revealed as a key and rich source of manifold nutritional and bioactive components. These include polyphenols, flavonoids, organic acids, hydroxybenzoic, hydroxycinnamic acid derivatives, (epi) catechin derivatives, pro-anthocyanidins, procyanidins, quercetin derivatives. AVDP possessed enriched nutritional profiles ranging from protein, carbohydrate, lipids, fibers, and ashes, with various applications in the medicinal, cosmetics, and food industry. Bioactive components in the AVDP have been linked with several pharmacological properties, like antioxidants, anti-inflammatory, and antimicrobial. The enriched nutritional profile has confirmed AVDP utilization in the food industry as a functional food, food additives, feed formulations, and preservatives. Hence, the valorization of this AVDP recycling to produce diverse materials with potential industrial and medicinal impact is necessary. This review will focus on the nutritional profile and bioactive components of the AVDP, its pharmacological and food industrial applications.